Reimagining the Nation State : The Contested Terrains of Nation-Building - Mac Laughlin, Jim (London Pluto Press, 2001)
Using Ireland as a case study, this book provides a reassessment of established models of nationalism and nation building. The author argues for a grassroots, place-centred approach, and assesses competing models in the works of key theorists such as Gellner, Hecter, Nairn and Smith.
Include Bibliography and Index
Keywords: Ireland -- Nationalism -- National characteristics, Irish -- Irish question -- Politics and government